The Transformation of the Concept of an Urban Ecosystem: Classical and Modern Urban Ecology - Žiemelis, Darius (Sociologija. Mintis ir veiksmas, 2018)
Contemporary trends in urban development indicate that its processes rarely observe ecocentric perspectives, under which nature is considered as a value. This concept is represented by modern urban ecology. Meanwhile, the urban ecosystem, as a concept of a human system, is represented by classical urban ecology. The existence of different urban ecosystem concepts encourages a closer look at not only the differences between these concepts but also the circumstances that have led to this transformation process. The aim of this article is to analyze the concepts of an urban ecosystem in classical and modern urban ecology, focusing not only on the explication of the content of the concepts of urban ecosystem, but also on the social, cultural and economic conditions of the emergence of different concepts. This article reveals that the separation of urban ecosystem concepts was determined by the different sociocultural environment in which classical urban ecology and contemporary urban ecology have emerged. From the point of view of modern urban ecology, in order to explain the reasons for the emergence of global urban development problems and to search for solutions to them, the conceptual legacy of classical urban ecology, due to its anthropocentric orientation, not only cannot be of use anymore but also hinders in this search – that is, instead of solving problems, it makes them even worse.